GARUDA APP (Generasi Aktif, Responsif, Unggul Dan Adaptif) : Inovasi Mendukung Penguatan Keterampilan Abad-21 Dalam Pembelajaran Mendalam - Soni Ariatama; Sawalludin; Sutrimo (Advances In Education Journal, 2025)
The development of 6C skills (Critical Thinking, Creative Thinking, Collaboration, Communication, Character, Citizenship) in students in the current era is very important in the learning process at school because these skills are not just complementary but are the foundation for individual and national success in facing global challenges. The objectives of this study are to reveal: 1) Issues related to 21st-century skills, 2) Schools' efforts to support the strengthening of 21st-century skills, 3) Teachers' media in providing reinforcement of 21st-century skills at SMP Negeri 1 Belitang Madang Raya. This research uses the Research and Development (RnD) method. The data collection techniques used are observation, questionnaires, and interviews. The data analysis techniques used were data collection, data reduction, and data presentation. The results of this study are 1) The contribution of teachers and schools in supporting the strengthening of students' 21st-century skills, 2) School efforts in providing 21st-century skills reinforcement through an Android application as a supplement to in-depth and meaningful learning, 3) The creation of the Garuda APP (Active, Responsive, Excellent, and Adaptive Generation) media, which received interactive and interesting responses from students and was very helpful for teachers.